Strategies For Developing Educators' Competencies To Create An Effective Learning Environment In Higher Education - Susilo Surahman (Linguanusa : Social Humanities, Education and Linguistic, 2023)
Introduction to The Problem: This states the core problem of the article in a concise and concise manner Purpose: This research identifies the core competencies that educators should possess, including pedagogical ability, content mastery, and interpersonal and technological skills. Furthermore, the importance of continuous professional development and a supportive educational environment is discussed. Design/methods/approach: Through a qualitative approach, this article explores various methods and best practices that educators can apply to improve teaching quality. Findings: The results showed that developing educators' competencies improved the quality of learning and strengthened student engagement and motivation. Research implications/limitations: Here, you can explain characteristics of design or methodology that impacted or influenced the interpretation of the findings from your research. They are the constraints on generalizability, applications to practice, and utility of findings that result from how you initially chose to design the study or the method used to establish internal and external validity of the result of unanticipated challenges that emerged during the study. Your research may have multiple limitations, but you need to discuss only those directly related to your research problems. Originality/value: This article provides strategic recommendations for higher education institutions in designing professional development programs that are effective and responsive to the needs of educators and students.